VALUASI EKONOMI AIR DI HUTAN LARANGAN ADAT KENEGERIAN RUMBIO DESA PULAU SARAK KECAMATAN KAMPAR KABUPATEN KAMPAR - Sribudiani, Evi; ', Arfitryana; ', Mukhamadun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Forests have a variety of benefits that can be felt by every living creature. The benefits consist of real measurable benefits (tangible) and intangible benefits (intangible).One of theimportant environmentalbenefitsofforestsarehydrologicalbenefits. One example ofthe use ofwater sourcedfromthe forestisin the forest ofProhibitionForestKenegerianRumbio. Ithas springswithgood quality. The communitiesuse itforvarious purposessuch asforhouseholdconsumption, fisheries, anddirect trading. Wateras aresourcethat isstillvalued as intangible, it is stilldifficult to assessthemarketsystem. This studyaims to determine theeconomic valuationof water at TraditionalProhibitionForest Kenegerian Rumbio Pulau Sarak Village of KamparÂ District Kampar Regency. This research was conductedbyusing themethod ofmarketprice approachorproductivityof thecommoditywhich is related each other. The market priceisusedto determine thenet priceorrentunitsofwideuse ofnatural resources. The results showedthe economicvaluationof waterat TraditionalProhibitionForest Kenegerian RumbioisRp.5.865.814.050peryear, with atotaleconomic valueofRp.53.298.227.751for 25years. Â Keywords: Forest, Water, Valuation.